Penyesuaian Akademik Mahasiswa Pendatang dari Daerah 3T (Terdepan, Terluar, Tertinggal): Bagaimana Peran Asertivitas dan Kecerdasan Kultural? - Rahayu, Maria Nugraheni Mardi (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2025)
Students' academic adjustment in the early years of college presents unique challenges for those from 3T areas (Frontier, Outermost, Disadvantaged). Successful academic adjustment for these students requires certain supporting skills. This study examines the role of assertiveness and cultural intelligence in academic adjustment among students from 3T areas. A total of 80 first- and second-year students from 3T areas at a private university in Salatiga participated (61.25% female, M_age = 20.47 years, SD = 1.66 years). The instruments used were the Assertiveness Formative Questionnaire, the Cultural Quotient Scale, and the Academic Adjustment subscale of the Student's Adjustment to College Questionnaire. Data were analyzed using multiple linear regression. The results indicated that: 1) Assertiveness and cultural intelligence both play a role in the academic adjustment of students from 3T areas; 2) Assertiveness significantly affects academic adjustment; 3) Cultural intelligence does not significantly affect academic adjustment. Based on these findings, faculties and universities should implement programs to support students from 3T areas in their academic adjustment, focusing on enhancing assertiveness skills.